Carbon / carbon composite material surface anti-silicification high-temperature-oxidation-resistant CrSi2-SiC-Si / SiC composite coating and preparation method thereof
By preparing CrSi2-SiC-Si/SiC composite coating on the surface of C/C composite, the problem of easy oxidation of C/C composite materials in high-temperature aerobic environment is solved, and its high-temperature oxidation protection and mechanical properties are significantly improved.
Patent Information
- Application Number
- CN202411777024.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-18
Smart Images

Figure CN119841666A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature anti-oxidation, and in particular to a carbon / carbon surface anti-siliconization and high-temperature oxidation resistant CrSi2-SiC-Si / SiC composite coating and a preparation method thereof. Background Art
[0002] Carbon / carbon (C / C) composites have low density (<2.2g / m 3 ), low thermal expansion coefficient (~1×10 -6 / K), high temperature resistance (~3573K), excellent heat shock resistance and excellent mechanical properties in high temperature inert atmosphere, etc., C / C composites are widely used in high temperature structural components in the aerospace field; however, the inherent oxidation sensitivity of C / C composites makes it difficult for their excellent properties to be brought into play in high temperature aerobic environments. In an aerobic environment above 400℃, C / C composites will be oxidized and corroded, resulting in a significant decrease in their mechanical properties, which limits the application of C / C composites in the aerospace field. The preparation of anti-oxidation coatings is one of the effective ways to solve this problem. Among them, the silicon-based ceramic system has good physical and chemical compatibility with C / C composites, and the SiO2 generated by its oxidation reaction at high temperature has an extremely low oxygen diffusion coefficient (10 at 1473K). -13 g cm -1 s -1 , 10 at 2473K -11 g cm -1 s -1 ), which can provide effective oxidation protection for C / C composites.
[0003] Reference 1 "QGFu, HJLi, XHShi, et al. Silicon carbide coating to protect carbon / carbon composites against oxidation [J]. Scripta materialia, 2005, 52 (9): 923-927." A SiC coating was prepared on the surface of a C / C composite by a two-step embedding method. The coating can effectively protect the C / C composite for up to 310 hours at 1773K. However, the mass loss of the SiC-coated C / C composite was as high as 4.7% after exposure to 1973K for 3 hours. This is because the increase in temperature causes the stability of the SiO2 protective film to decrease. In order to improve the service life and temperature of silicon-based ceramic coatings, ultra-high temperature ceramic borides are introduced into silicon-based coatings as another type of material with high melting point, good thermochemical stability and stronger temperature resistance.
[0004] Reference 2 "XRRen, HJLi, YHChu, et al. Ultra-high-temperature ceramic HfB2-SiC coating for oxidation protection of SiC-coated carbon / carbon composites [J]. International Journal of Applied Ceramic Technology, 2015, 12 (3): 560-567." The HfB2-SiC coating was prepared on the C / C composite by an in-situ reaction method. After oxidation in air at 1773K for 265 hours, the weight loss was only 0.41×10-2g / cm 2 However, due to the introduction of ultra-high temperature ceramics, the preparation temperature of the coating is high (2173-2373K), the preparation time is long (2-3h), and the thermal expansion coefficient of ultra-high temperature ceramics is quite different from that of the C / C matrix. Therefore, the stress of the coating is large, which is prone to thermal stress concentration and induces cracking. Summary of the invention
[0005] In order to avoid the shortcomings of the prior art, the present invention proposes a C / C composite material having a CrSi2-SiC-Si / SiC composite coating on the surface that is resistant to siliconization and high temperature oxidation and a preparation method thereof. The technical solution of the present invention is as follows:
[0006] A CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high-temperature oxidation resistance on the surface of a C / C composite material. The composite coating comprises a SiC transition layer and a CrSi2-SiC-Si outer coating. The SiC transition layer covers the C / C composite material, and the outer coating covers the transition layer.
[0007] As an improvement, a PyC layer is provided on the surface of the C / C composite material, and the SiC transition layer covers the PyC layer.
[0008] The preparation method of the present invention comprises the following steps:
[0009] Step 1: placing the C / C composite material in a deposition furnace, and depositing a pore-sealing PyC layer on its surface to obtain a C / C composite material with a PyC layer on the surface;
[0010] Step 2: Weigh Si, C and Al2O3 powders and mix them evenly;
[0011] Step 3: embedding the C / C composite material with a PyC layer on the surface obtained in step 1 into the mixed powder obtained in step 2, and heat treating it under the protection of an inert atmosphere to obtain a C / C composite material coated with a SiC layer;
[0012] Step 4: quantitatively weigh Cr, Si, SiC powder and polyvinyl butyral (PVB) solution, add anhydrous ethanol, and mix well to obtain slurry;
[0013] Step 5: Evenly apply the slurry obtained in step 4 on the surface of the composite material obtained in step 3, repeat this step several times to obtain the desired thickness, and then dry it for later use;
[0014] Step 6: heat-treating the sample obtained in step 5 under the protection of an inert atmosphere;
[0015] Step 7: Weigh a certain amount of Si and C powder, mix them evenly to obtain a powder, bury the sample obtained in step 6 in the mixed powder, and heat treat it under the protection of an inert atmosphere to obtain a C / C composite material with an anti-siliconization and high-temperature oxidation-resistant CrSi2-SiC-Si / SiC composite coating on the surface.
[0016] As an improvement, the mass ratio (wt%) of Si:C:Al2O3 in step 2 is (70-80):(10-20):(10-20).
[0017] As an improvement, in step 3, the heat treatment temperature is 2073-2373 K, the insulation time is 1-3 h, and the heating rate is 5-10 K / min.
[0018] As an improvement, in step 4, the mass ratio (wt%) of Cr, Si, SiC powder, polyvinyl butyral (PVB) solution, and anhydrous ethanol is (30-35):(10-15):(10-15):(1-2):(40-65).
[0019] As an improvement, in step 6, the heat treatment temperature is 1773-1873 K, the insulation time is 1-2 h, and the heating rate is 5-10 K / min.
[0020] As an improvement, in step 7, the mass ratio (wt%) of Si and C powder is (90-95):(5-10), the heat treatment temperature is 1773-1873K, the insulation time is 1-2h, and the heating rate is 5-10K / min.
[0021] As an improvement, the thickness of the slurry applied in step 5 is 80 to 150 μm.
[0022] The advantages of the present invention are:
[0023] 1. The present invention arranges a CrSi2-SiC-Si layer on the surface of the C / C composite material. The Cr2O3 formed by CrSi2 at high temperature can act as a "pinning phase" to inhibit the generation and expansion of microcracks, and the formed SiO2 can repair the microcracks of the coating. In addition, Cr can be doped into the SiO2 lattice structure, thereby improving the bonding force between the SiO2 interfaces, so that the stability of the SiO2 lattice during the oxidation process is improved. In addition, Cr2O3 can form a stable network structure with SiO2 glass, thereby improving the high-temperature stability of the multiphase glass. The synergistic effect of Cr2O3 and SiO2 makes the C / C composite material long-life and resistant to high-temperature oxidation.
[0024] 2. The present invention sets a SiC transition layer between the C / C composite material and the CrSi2-SiC-Si coating, which can effectively alleviate the mismatch of thermal expansion coefficients between the CrSi2-SiC-Si coating and the C / C matrix, and reduce the thermal stress in the coating. Avoid the occurrence of cracking caused by the concentration of thermal stress in the coating. Then, the slurry is applied and combined with in-situ reaction sintering to prepare a CrSi5-CrSi-SiC coating with strong bonding force. Finally, the molten silicon generated in the embedding infiltration process is diffused with the CrSi5-CrSi to generate CrSi2 with better oxidation resistance, and the molten silicon fills the defects in the coating.
[0025] 3. The present invention pre-deposit a PyC layer on the surface of the C / C composite material before preparing the transition layer. The PyC layer can fill the internal defects of the C / C composite material, making the C / C surface structure dense and homogeneous in composition. At the same time, the PyC layer effectively prevents molten silicon from penetrating into the C / C matrix when the embedded melt-infiltrated SiC transition layer is embedded, avoids the silicification damage of the embedded melt-infiltrated SiC coating to the C / C composite material, and improves the mechanical properties of the C / C composite material in the coating.
[0026] 4. The CrSi2-SiC-Si / SiC coating C / C composite material prepared by the present invention has a mass loss of only 1.44% after being oxidized at 1773K for 530h. The coating remains intact after being oxidized at 1973K for 23h. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a process flow chart of the present invention.
[0028] Figure 2 Microstructure and XRD spectrum of the CrSi2-SiC-Si / SiC coating C / C composite material prepared in Example 1 of the present invention: (a) surface SEM image; (b) XRD spectrum; (c) cross-sectional BSD image.
[0029] Figure 3The oxidation mass change curves of the CrSi2-SiC-Si / SiC coating C / C composite material prepared in Example 1 of the present invention at different temperatures: (a) 1773K, (b) 1973K.
[0030] Figure 4 This is a SEM image of the CrSi2-SiC-Si / SiC coating C / C composite material prepared in Example 1 of the present invention after oxidation at 1773K for 530h.
[0031] Figure 5 This is a SEM image of the coating C / C composite material prepared in comparative example 1 of the present invention (without CrSi2-SiC-Si) after oxidation at 1773K for 120h. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiment 1 is only a part of the embodiments of the present invention, not all of the embodiments.
[0033] Example 1
[0034] A CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high temperature oxidation resistance on the surface of a C / C composite material and a preparation method thereof, comprising the following steps:
[0035] Step 1: Place the cleaned C / C composite material in a deposition furnace, deposit a pore-sealing PyC layer on its surface, cool the furnace to room temperature and take a sample to obtain a C / C composite material with a PyC surface layer;
[0036] Step 2: Weigh 75wt% Si powder, 15wt% C powder and 10wt% Al2O3 powder and place them in a ball mill, mix them on a ball mill for 6 hours, sieve out the mixed powder and dry it for later use.
[0037] Step 3: embed the PyC-C / C composite material sample in the mixed powder obtained in step 2 in a graphite crucible and cover the crucible, then place the crucible containing the sample in a high-temperature heat treatment furnace, heat it to 2373K at 10K / min under inert atmosphere protection, keep it warm for 2h, cool it to room temperature with the furnace and take a sample to obtain a C / C composite material coated with a SiC layer;
[0038] Step 4: Weigh 30wt% Cr, 15wt% Si, 10wt% SiC powder and 2wt% polyvinyl butyral (PVB) solution, add 48wt% anhydrous ethanol to prepare slurry, put the mixed slurry into a ball mill and mix well for later use;
[0039] Step 5: Evenly apply the mixed slurry obtained in step 4 on the SiC-C / C sample obtained in step 3, repeat this step several times to obtain the desired thickness, and then dry it in an oven for later use;
[0040] Step 6: Place the sample obtained in step 5 into a high-temperature tube furnace and heat it to 1273K at 5K / min under argon protection, then heat it to 1773K at 3K / min, keep it warm for 1.5h, cool it to room temperature with the furnace, and take out the sample for use;
[0041] Step 7: Weigh 95wt% Si and 5wt% C powder, mix them evenly and put them into a graphite crucible, and bury the sample obtained in step 6 in the mixed powder. Then put the graphite crucible into a high-temperature heat treatment furnace and heat it to 1273K at 5K / min under inert gas protection, then heat it to 1773K at 3K / min, keep it warm for 1.5h, cool it to room temperature with the furnace, take out the sample, and obtain a CrSi2-SiC-Si multiphase ceramic coating.
[0042] from Figure 2 It can be seen from a that the coating is a multiphase mosaic structure, mainly composed of CrSi2, SiC and a small amount of Si ( Figure 2 b). Backscattered SEM image of the coating cross section ( Figure 2 c) It can be seen that the coating is a dense oxide layer consisting of a SiC transition layer with a thickness of 100 μm and a CrSi2-SiC-Si coating with a thickness of 110 μm.
[0043] from Figure 3 It can be seen that the mass loss of the prepared CrSi2-SiC-Si / SiC coating C / C composite material sample after oxidation at 1773K for 530h is only 1.44%, showing excellent anti-oxidation performance.
[0044] from Figure 4 It can be seen that after the prepared CrSi2-SiC-Si / SiC coating C / C composite material was oxidized at 1773K for 530h, some holes appeared on the coating surface, and the coating was relatively intact. Therefore, the CrSi2-SiC-Si / SiC coating can provide at least 530h of oxidation protection for the C / C composite material at 1773K.
[0045] Comparative Example 1
[0046] A SiC coating for preventing silicification on the surface of a C / C composite material and a preparation method thereof, comprising the following steps:
[0047] Step 1: Place the cleaned C / C composite material in a deposition furnace, deposit a pore-sealing PyC layer on its surface, cool the furnace to room temperature and take a sample to obtain a C / C composite material with a PyC surface layer;
[0048] Step 2: Weigh 75wt% Si powder, 15wt% C powder and 10wt% Al2O3 powder and place them in a ball mill, mix them on a ball mill for 6h, sieve out the mixed powder and dry it for later use.
[0049] Step 3: embed the PyC-C / C composite material sample in the mixed powder obtained in step 2 in a graphite crucible and cover the crucible, then place the crucible containing the sample in a high-temperature heat treatment furnace, heat it to 2373K at 10K / min under inert atmosphere protection, keep it warm for 2h, cool it to room temperature with the furnace and take a sample to obtain a C / C composite material coated with a SiC layer;
[0050] from Figure 5 It can be seen that after the SiC coating C / C composite material was oxidized at 1773K for 120h, large-sized holes (>100μm) appeared on the coating surface, which provided direct channels for oxygen penetration, resulting in oxidation and failure of the C / C matrix. Therefore, the SiC coating cannot provide long-term oxidation protection for the C / C composite material.
[0051] Example 2
[0052] A CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high temperature oxidation resistance on the surface of a C / C composite material and a preparation method thereof, comprising the following steps:
[0053] Step 1: Place the cleaned C / C composite material in a deposition furnace, deposit a pore-sealing PyC layer on its surface, cool the furnace to room temperature and take a sample to obtain a C / C composite material with a PyC surface layer;
[0054] Step 2: Weigh 80wt% Si powder, 10wt% C powder and 10wt% Al2O3 powder and place them in a ball mill, mix them on a ball mill for 6h, sieve out the mixed powder and dry it for later use.
[0055] Step 3: embed the PyC-C / C composite material sample in the mixed powder obtained in step 2 in a graphite crucible and cover the crucible, then place the crucible containing the sample in a high-temperature heat treatment furnace, heat it to 2073K at 5K / min under inert atmosphere protection, keep it warm for 3h, cool it to room temperature with the furnace and take a sample to obtain a C / C composite material coated with a SiC layer;
[0056] Step 4: Weigh 30wt% Cr, 15wt% Si, 10wt% SiC powder and 2wt% polyvinyl butyral (PVB) solution, add 43wt% anhydrous ethanol to prepare slurry, put the mixed slurry into a ball mill and mix well for later use;
[0057] Step 5: Evenly apply the mixed slurry obtained in step 4 on the SiC-C / C sample obtained in step 3, repeat this step several times until the coating thickness reaches 150 μm, and then dry it in an oven for later use;
[0058] Step 6: Place the sample obtained in step 5 into a high-temperature tube furnace and heat it to 1273K at 5K / min under argon protection, then heat it to 1773K at 3K / min, keep it warm for 1.5h, cool it to room temperature with the furnace, and take out the sample for use;
[0059] Step 7: Weigh 90wt% Si and 10wt% C powder, mix them evenly and put them into a graphite crucible, and bury the sample obtained in step 6 in the mixed powder. Then put the graphite crucible into a high-temperature heat treatment furnace and heat it to 1273K at 10K / min under inert gas protection, then heat it to 1873K at 3K / min, keep it warm for 1h, cool it to room temperature with the furnace, take out the sample, and obtain a CrSi2-SiC-Si multiphase ceramic coating.
[0060] Example 3
[0061] A CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high temperature oxidation resistance on the surface of a C / C composite material and a preparation method thereof, comprising the following steps:
[0062] Step 1: Place the cleaned C / C composite material in a deposition furnace, deposit a pore-sealing PyC layer on its surface, cool the furnace to room temperature and take a sample to obtain a C / C composite material with a PyC surface layer;
[0063] Step 2: Weigh 70wt% Si powder, 20wt% C powder and 10wt% Al2O3 powder and place them in a ball mill, mix them on a ball mill for 6 hours, sieve out the mixed powder and dry it for later use.
[0064] Step 3: embed the PyC-C / C composite material sample in the mixed powder obtained in step 2 in a graphite crucible and cover the crucible, then place the crucible containing the sample in a high-temperature heat treatment furnace, heat it to 2073K at 5K / min under inert atmosphere protection, keep it warm for 3h, cool it to room temperature with the furnace and take a sample to obtain a C / C composite material coated with a SiC layer;
[0065] Step 4: Weigh 35wt% Cr, 10wt% Si, 14wt% SiC powder and 1wt% polyvinyl butyral (PVB) solution, add 40wt% anhydrous ethanol to prepare slurry, put the mixed slurry into a ball mill and mix well for later use;
[0066] Step 5: Evenly apply the mixed slurry obtained in step 4 on the SiC-C / C sample obtained in step 3, repeat this step several times to obtain a coating thickness of 80 μm, and then dry it in an oven for later use;
[0067] Step 6: Place the sample obtained in step 5 into a high-temperature tube furnace and heat it to 1273K at 5K / min under argon protection, then heat it to 1773K at 3K / min, keep it warm for 1.5h, cool it to room temperature with the furnace, and take out the sample for use;
[0068] Step 7: Weigh 90wt% Si and 10wt% C powder, mix them evenly and put them into a graphite crucible, and bury the sample obtained in step 6 in the mixed powder. Then put the graphite crucible into a high-temperature heat treatment furnace and heat it to 1273K at 10K / min under inert gas protection, then heat it to 1873K at 3K / min, keep it warm for 2h, cool it to room temperature with the furnace, take out the sample, and obtain a CrSi2-SiC-Si multiphase ceramic coating.
[0069] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high temperature oxidation resistance on the surface of a carbon / carbon composite material, characterized in that: The composite coating comprises a SiC transition layer and a CrSi2-SiC-Si outer coating, wherein the SiC transition layer is covered on the carbon / carbon composite material, and the outer coating is covered on the transition layer.
2. The CrSi2-SiC-Si / SiC composite coating with anti-siliconization and high temperature oxidation resistance on the surface of carbon / carbon composite material according to claim 1, characterized in that: A PyC layer is provided on the surface of the carbon / carbon composite material, and the SiC transition layer covers the PyC layer.
3. A method for preparing a CrSi2-SiC-Si / SiC composite coating on the surface of a carbon / carbon composite material that is resistant to siliconization and high temperature oxidation, characterized in that: The steps include: Step 1: placing the carbon / carbon composite material in a deposition furnace, and depositing a pore-sealing PyC layer on the surface thereof to obtain a carbon / carbon composite material with a PyC layer on the surface; Step 2: Weigh Si, C and Al2O3 powders and mix them evenly; Step 3: embedding the carbon / carbon composite material with a PyC layer on the surface obtained in step 1 into the mixed powder obtained in step 2, and heat treating it under the protection of an inert atmosphere to obtain a carbon / carbon composite material coated with a SiC layer; Step 4: quantitatively weigh Cr, Si, SiC powder and polyvinyl butyral (PVB) solution, add anhydrous ethanol, and mix well to obtain slurry; Step 5: Evenly apply the slurry obtained in step 4 on the surface of the composite material obtained in step 3, repeat this step several times to obtain the desired thickness, and then dry it for later use; Step 6: heat-treating the sample obtained in step 5 under the protection of an inert atmosphere; Step 7: Weigh a certain amount of Si and C powder, mix them evenly to obtain a powder, bury the sample obtained in step 6 in the mixed powder, and heat treat it under the protection of an inert atmosphere to obtain a carbon / carbon composite material with an anti-siliconization and high-temperature oxidation-resistant CrSi2-SiC-Si / SiC composite coating on the surface.
4. The preparation method according to claim 3, characterized in that: In step 2, the mass ratio (wt%) of Si:C:Al2O3 is (70-80):(10-20):(10-20).
5. The preparation method according to claim 3, characterized in that: In step 3, the heat treatment temperature is 2073-2373 K, the insulation time is 1-3 h, and the heating rate is 5-10 K / min.
6. The preparation method according to claim 3, characterized in that: In step 4, the mass ratio (wt%) of Cr, Si, SiC powder, polyvinyl butyral (PVB) solution and anhydrous ethanol is (30-35):(10-15):(10-15):(1-2):(40-65).
7. The preparation method according to claim 3, characterized in that: In step 6, the heat treatment temperature is 1773-1873 K, the insulation time is 1-2 h, and the heating rate is 5-10 K / min.
8. The preparation method according to claim 3, characterized in that: In step 7, the mass ratio (wt%) of Si and C powder is (90-95):(5-10), the heat treatment temperature is 1773-1873K, the insulation time is 1-2h, and the heating rate is 5-10K / min.
9. The preparation method according to claim 3, characterized in that: The thickness of the slurry applied in step 5 is 80 to 150 μm.